algebraic proofs of Fermats last theorem and Beals conjecture - Joseph, James E (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, the following statememt of Fermats Last Theorem is proved. If x, y, z are positive integersï° is an odd prime and z = x y , x, y, z ï° ï° ï° ï€« are all even. Also, in this paper, is proved (Beals conjecture) The equation ï¸ ï ï® z = x ï€« y has no solution in relatively prime positive integers x, y, z, with ï¸ ,ï,ï® primes at least .